(untitled) (De Rebus Antiquis, 2021)
Augustus, considered by many to be the first Roman Emperor, is the focus of numerous analyzes, which, in turn, exposes numerous facets of this ruler. This article proposes a brief essay about how discursive images and material creations, such as coins, were fundamental to legitimize the power of this Princeps, his representations and representativeness.